Analysis of Strength, Stiffness, and Stability The Formwork Construction in LRT Jabodebek Project - Munthe, Agyanata Tua; Noegroho, Muhammad Ardiansyah (NAROTAMA UNIVERSITY, Indonesia, 2020)
The Upper Longitudinal Beam casting on the Jabodebek LRT Project requires a shoring to be able to withstand the workloads. To avoid the failure of formwork construction, formwork must meet the strength, stiffness, and stability requirements for each formwork component material. The analysis is carried out on the value of bending stress, deflection, and shear that occur in each component of formwork. From the analysis carried out each obtained as follows. Strength requirements with flexural stress values that occur in Plywood, Girder GT 24, and Steel Waller SRZ materials, each of which is smaller than ? permit = 100 kg / cm2, 70000 kg / cm2, and 1200 kg / cm2. Stiffness requirements with deflection values that occur on Plywood and Girder GT 24 material are ? permit = l / 400. Whereas the SRZ Steel Waller fulfills ? permit = l / 240. Stability requirements with shear stress values that occur in Plywood, Girder GT 24, and Steel Waller SRZ materials, each of which is smaller than ? permit = 12 kg / cm2, 1400 kg / cm2, and 696 kg / cm2. Peri Up Shoring can support all formwork loads. So it can be said that the construction of the Upper Longitudinal Beam formwork is in a safe condition.